Sexually transmitted infections among Pakistani pregnant women and their husbands in Norway - Soen Eng Yap Bjerke; Ellen Holter; Siri Vangen; et al (Dove Medical Press, 2010)
Soen Eng Yap Bjerke1,2, Ellen Holter3, Siri Vangen2,4, Babill Stray-Pedersen1,21Medical Faculty, University of Oslo, Oslo, Norway; 2Women and Children’s Division, 3Department of Microbiology, Oslo University Hospital, Rikshospitalet, Oslo, Norway; 4National Resource Centre for Women’s Health, Oslo, NorwayAim: To assess frequency and determine the factors associated with Chlamydia trachomatis, herpes simplex virus type 2, and hepatitis B seropositivity among Pakistani pregnant women and their husbands in Norway.Methods: All together 112 couples of Pakistani origin living in Norway participated in our study. Blood samples were tested for immunoglobulin G (IgG) antibodies against C. trachomatis, herpes simplex virus type 2, and hepatitis B.Results: Pakistani women had significantly lower age, education level, and years of residence in Norway compared to their male partners. Among the men, 12% had positive chlamydial IgG antibodies in contrast to 1% of the women. These couples were discordant, meaning that the 13 wives of positive men were not infected with C. trachomatis, and the husband of one positive woman was not infected either. Four percent of women and 2% of men were positive for herpes simplex type 2. Only one couple was concordantly positive for herpes simplex type 2, the remaining four couples were discordant. Twelve percent of women and 21% of men were, or had been, infected with hepatitis B.Conclusion: Sexually transmitted infections did not seem to be prevalent in Pakistani immigrant couples in Norway. However, it was striking that most couples were discordant. Pakistani immigrants should be offered hepatitis B vaccine.Keywords: Chlamydia trachomatis, herpes simplex virus type 2, hepatitis B, Pakistan, Norway